Tikkun K’nessiah: Repairing the Church - Rees, Robert A. (Dialogue, 2020)
It isn't the Church of the First Presidency or the Quorum of the Twelve or the General Authorities, it isn't the Church of conservatives or liberals or of any particular group, but rather the Church of all those who are or can be called saints. 4) Related to and reflective of this imbalance is the perception that the dominant culture influencing the Church on matters of war and peace, the environment, social justice, immigration, politics, and Church polity is the culture of the Intermountain W est, especially Utah. TIKKUN K'NESSIAH: REPAIRING THE CHURCH. 109 TIKKUN K'NESSIAH: REPAIRING THE CHURCH Robert A. Rees I believe "Mormonism" ... calls for thoughtful disciples who will not be content with merely repeating some of its truths, but will develop its truths; and enlarge it by that development.